2020
DOI: 10.1002/2211-5463.12871
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 metabolism mediates low‐temperature resistance in pinewood nematode

Abstract: Pinewood nematode (PWN; Bursaphelenchus xylophilus) is a devastating invasive species that is expanding into colder regions. Here, we investigated the molecular mechanisms underlying low‐temperature resistance of PWN. We identified differentially expressed genes enriched under low temperature in previously published transcriptome data using the Kyoto Encyclopedia of Genes and Genomes. Quantitative real‐time PCR was used to further validate the transcript level changes of three known cytochrome P450 genes under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…On the other hand, population splitting analysis reveals that the genetic variations among different strains are possibly induced by temperature and precipitation while those two environmental factors normally interact with each other. Meanwhile, relevant studies usually indicate that temperature is important for the adaptation and survival of B. xylophilus 65–68 . This identification may suggest that the nematodes could evolve to adapt to different environments to expand their populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, population splitting analysis reveals that the genetic variations among different strains are possibly induced by temperature and precipitation while those two environmental factors normally interact with each other. Meanwhile, relevant studies usually indicate that temperature is important for the adaptation and survival of B. xylophilus 65–68 . This identification may suggest that the nematodes could evolve to adapt to different environments to expand their populations.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, relevant studies usually indicate that temperature is important for the adaptation and survival of B. xylophilus . 65 , 66 , 67 , 68 This identification may suggest that the nematodes could evolve to adapt to different environments to expand their populations. The hypothesis is further confirmed by nonsynonymous SNPs (geographically associated) found on signaling‐related genes like GPCR families.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, with the strengthening of full-scale trade, B. tabaci MEAM cryptic species successfully invaded China with the help of flowers and other cash crops and is now widely distributed across most provinces [10]. Many studies have indicated that the temperature adaptation processes of B. tabaci are regulated at the molecular level [12][13][14][15][16]. In a temperature adaptability study of B. tabaci, it was found that the whitefly can quickly adapt to a new environment when entering a new habitat, and its temperature tolerance has produced corresponding transient genetic changes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that some insects respond to lowtemperature environments by promoting the expression of genes encoding cold resistance substances such as trehalose, HSPs, antioxidant enzymes and enzymes related to the synthesis and degradation of cryoprotectants [46][47][48]. HSPs are molecular chaperones produced by organisms in response to an environmental pressure that help correct the folding of amino acid chains and participate in the transmembrane transport of proteins [49].…”
Section: Discussionmentioning
confidence: 99%